Gender Links and Non-Syndrome Related Mutations Linking Isolated Cleft Palate and Ankyloglossia in the Fetal Development - Hodge King, Dana; Kaminiorz, Sven David Stefan; Patterson, Bethany Marie (Archive of Orofacial Data Science, 2024)
AIM: To compare the pathogenesis of ankyloglossia (tongue-tie) with isolated cleft palate only (CPO) by examining the influence of genetic and epigenetic factors. METHODS: A comprehensive literature review encompassing the years 2012-2017, yielded a substantial body of research linking cleft palate and ankyloglossia. Inclusion criteria comprised randomized controlled clinical trials, both prospective and retrospective; with the exclusion of non-English studies. RESULTS: The embryonic parallels between CPO and ankyloglossia suggest a phenotypic expression through neural crest cells along the anterior-posterior axis. These developmental pathways persist during palatogenesis, affecting structures such as palatal shelves and the lingual frenum. Significantly, the cranial neural crest derived connective tissue of the lingual frenum demonstrates a functional correlation with the genioglossus muscle. In the context of cleft palate (CP) models, malformation of the genioglossus muscle is associated with micrognathia in extrinsic perspectives, while intrinsic perspectives focus on causal genes affecting palatal shelves. Ankyloglossia is identified as part of an X-linked, gender-specific disease spectrum with various midline-related variations along the anterior-posterior axis. CONCLUSION: The functional perspective has brought attention to the interplay of structures surrounding the palate in comprehending CP etiology. This approach underscores the importance of tongue position and the attachment of the lingual frenum connective tissue to the genioglossus muscle. Early intervention aimed at reducing the lingual frenum may potentially enhance the form and function of the oral cavity.